Analisis Struktur Kinerja dan Konsep Keunggulan Komparatif Industrialisasi di Indonesia - Elvira Dinda Kurniasari; Fandy Ardiansyah; Muhammad Yasin (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
Industrialization plays a critical role in the process of economic development, particularly in shaping a stronger and more competitive economic structure. For Indonesia, an industrialization strategy is not merely a tool for boosting economic growth, but a key instrument for promoting long-term structural transformation. This article discusses how industrialization strategies should be designed holistically, taking into account not only the manufacturing sector but also the interconnections with agriculture and services. Within the national development framework, the state must take an active role by implementing fiscal policies, providing infrastructure support, and offering incentives for value-added industries. Lessons from newly industrialized countries show that the success of industrialization is highly dependent on consistent policy coordination, strong leadership, and robust institutional capacity. Furthermore, industrial strategies must be responsive to global challenges such as technological change, international competition, and regional disparities. Therefore, industrial development planning in Indonesia should be oriented towards achieving economic efficiency, strengthening domestic production capabilities, generating broad employment opportunities, and ensuring equitable distribution of development benefits. This paper aims to provide a conceptual foundation for formulating a national industrialization strategy that is not only responsive to global trends but also capable of addressing domestic needs in an inclusive and sustainable manner.